Decomposition of organic impurities in sodium iodide - Sofronov, D.S.; Kisil', E.M.; Kudin, K.A.; Voloshko, A.Yu.; Shishkin, O.V. (Functional Materials, 2005)
The decomposition process of organic impurities present in the initial sodium iodide raw material has been studied using mass spectrometry. The decomposition has been found to result in formation of СО, СО₂, and various hydrocarbons. The decomposition of organic impurities is accompanied also by release of water that may be due both to direct decomposition of organic compounds and to oxidation thereof with oxygen present in the gas medium. Realization of the organic impurity oxidation at 400 to 450 ℃ provides the complete removal thereof from sodium iodide. Методом мас-спектрометрiї проведено дослiдження процесу розкладу органiчних примесей, що мiстяться у йодидi натрiю. Bстановлено, що в результатi їхнього термiчного розкладу формуються СО, СО₂, вуглець та вуглеводневi речовини рiзного складу CₙHₘ. Процес розкладу органiчних примесей супроводжується також видiленням молекул води, утворення яких може бути пов'язано як з їх безпосереднiм розкладом, так i з окислюванням присутнiм у газовому середовищi киснем. Проведення окислення органiчних сполук у температурному дiапазонi 400-450 ℃ дозволяє повнiстю вилучити їх з йодиду натрiю. Масс-спектрометрическим методом изучен процесс разложения органических примесей, присутствующих в исходном сырье йодида натрия. Установлено, что в результате их термического разложения образуется СО, СО₂, углерод и углеводороды различного состава CₙHₘ. Процесс разложения органических примесей сопровождается также выделением молекул воды, образование которых может быть связано как непосредственно с их разложением, так и их окислением в газовой среде кислородом. Проведение окисления органических примесей в диапазоне температур 400-450 ℃ позволяет полностью удалить их из йодида натрия.